5-Methyl-2,4-bis(methylsulfanyl)tricyclo[6.2.1.0(2,7)]undeca-4,9-diene -3,6-dione - von Richthofen, A.A.; Cardoso Filho, J.E.P.; Marzorati, L.; Zukerman-Schpector, J.; Tiekink, E.R.T.; Di Vitta, C. (International Union of Crystallography, 2010)
The structure analysis of the title compound, C14H16O2S2, shows the SMe and H atoms of the bond linking the six-membered rings to be syn and also to be syn to the bridgehead -CH2- group. Each of the five-membered rings adopts an envelope conformation at the bridgehead -CH2- group. The dione-substituted ring adopts a folded conformation about the 1,4-C center dot center dot center dot C vector, with the ketone groups lying to one side. The cyclohexene ring adopts a boat conformation.